REVOLUTIONIZING LANGUAGE TEACHING: THE ROLE OF ARTIFICIAL INTELLIGENCE (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The article provides general information about language phenomena, artificial intelligence and their connection with knowledge, thinking, memory, etc. In addition, the approaches and opinions of scientists on these topics are presented and explained with the help of examples. The author states that the movement of thinking and the formation of thought is associated with cognitive activity, a process that ensures the reflection of reality directly in the mind. It is known that the formation of speech units and their understanding are the result of mental activity. The performance of this activity is directly related to the condition of obtaining linguistic knowledge. There is no way to know reality without linguistic knowledge, to lyrically express logical structures that reflect information about the current event-events. However, at the intersection of cognitive science, six fields of science are adjacent, and a single scientific goal is to be occupied with the search for a solution to the problems of concentration, processing and application of knowledge in natural and artificial systems. It seems-that interrelation between these areas does not take place in the same way, whereas, Artificial Intelligence and anthropological philosophy are directly related. Meanwhile, human cognitive activity should be considered not as a reflection of being as a mirror, but as a phenomenon that reflects the inner or outer essence of objects. The mental structure formed in the process of cognition – the content of the concept is occupied by character-features that have a clear appearance of exactly this type, and the same features lead in the linguistic reality of the concept.